Temperature and thermal dose during radiotherapy and hyperthermia for recurrent breast cancer are related to clinical outcome and thermal toxicity: a systematic review. (1st January 2019) - Bakker, Akke; van der Zee, Jacoba; van Tienhoven, Geertjan; Kok, H. Petra; Rasch, Coen R. N.; Crezee, Hans
Abstract: Objective: Hyperthermia therapy (HT), heating tumors to 40–45 °C, is a known radiotherapy (RT) and chemotherapy sensitizer. The additional benefit of HT to RT for recurrent breast cancer has been proven in multiple randomized trials. However, published outcome after RT + HT varies widely. We performed a systematic review to investigate whether there is a relationship between achieved HT dose and clinical outcome and thermal toxicity for patients with recurrent breast cancer treated with RT + HT. Method: Four databases, EMBASE, PubMed, Cochrane library and clinicaltrials.gov, were searched with the terms breast, radiotherapy, hyperthermia therapy and their synonyms. Final search was performed on 3 April 2019. Twenty-two articles were included in the systematic review, reporting on 2330 patients with breast cancer treated with RT + HT. Results: Thirty-two HT parameters were tested for a relationship with clinical outcome. In studies reporting a relationship, the relationship was significant for complete response in 10/15 studies, in 10/13 studies for duration of local control, in 2/2 studies for overall survival and in 7/11 studies for thermal toxicity. Patients who received high thermal dose had on average 34% (range 27%–53%) more complete responses than patients who received low thermal dose. Patients who achieved higher HT parameters had increased odds/probability on improved clinical outcome and on thermal toxicity. Conclusion: Temperature and thermal dose during HT had significant influence on complete response, duration of local control, overall survival and thermal toxicity of patients with recurrent breast cancer treated with RT + HT. Higher temperature and thermal dose improved outcome, while higher maximum temperature increased incidence of thermal toxicity.